2022
DOI: 10.3389/fcimb.2022.871293
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome in Pancreatic Cancer-Implications for Diagnosis and Precision Bacteriophage Therapy for This Low Survival Disease

Abstract: While the mortality rates for many cancers have decreased due to improved detection and treatments, that of pancreatic cancer remains stubbornly high. The microbiome is an important factor in the progression of many cancers. Greater understanding of the microbiome in pancreatic cancer patients, as well as its manipulation, may assist in diagnosis and treatment of this disease. In this report we reviewed studies that compared microbiome changes in pancreatic cancer patients and non-cancer patients. We then iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 167 publications
0
3
0
Order By: Relevance
“…as well as Michaud et al [5,10]. Similarly Kabwe et al summarized latest literature regarding possible use of oral microbiomes as cancer markers, and found that it might be arduous to single out a specific bacteria universally linked to PC risks [18]. They also pointed out that comparing studies with different methodology is crucial to distinguish the connection of oral microbiome and PC, other than results drafted from oral wash samples only.…”
Section: Resultsmentioning
confidence: 99%
“…as well as Michaud et al [5,10]. Similarly Kabwe et al summarized latest literature regarding possible use of oral microbiomes as cancer markers, and found that it might be arduous to single out a specific bacteria universally linked to PC risks [18]. They also pointed out that comparing studies with different methodology is crucial to distinguish the connection of oral microbiome and PC, other than results drafted from oral wash samples only.…”
Section: Resultsmentioning
confidence: 99%
“…tested the vancomycin resistance in Veillonella strains from oral of healthy adults by agar dilution method ( Li et al., 2022 ). In the fecal samples, Prevotella , Streptococcus , and Klebsiella were the differential abundant microbes in the pancreatic cancer cohort compared with healthy cohort ( Kabwe et al., 2022 ). The genus Streptococcus has been studied for its association with cancer progression and treatment outcomes over an extended period ( Sobocki et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its use as an anti-tumor strategy should be carefully considered. Considering this, bacteriophage therapy is emerging as an alternative to precisely target specific bacteria associated with progression and poor prognosis in cancer, 30 , 142 , 143 but it has not been formally explored in PDAC yet.…”
Section: Microbiota Modulation Has Therapeutic Potential In Pdacmentioning
confidence: 99%